2023
DOI: 10.1029/2023wr034493
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Critical Zone Architecture and Snowpack on Streamflow Generation Processes: A Mountain‐Meadow Headwater System in a Mediterranean Climate

Abstract: Observations from a granitic watershed within a Mediterranean climate reveal the hydrologic and critical zone functioning of a perennial stream headwater and its upslope contributing area within a meadow system in the Sierra Nevada, California. Chemical analysis (diagnostic tools of mixing models, end member mixing analysis, tritium, etc.) and physical data (stream stage, piezometers, soil water, snowpack, etc.) indicate there are two primary pathways of water input into a headwater stream sourced from a mount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…The subsurface critical zone (CZ) structure has been invoked in their study to explain the observed overproduction of streamflow (Wlostowski et al., 2021). Similarly, other studies also used the subsurface CZ structure to explain various hydrologic observations in a number of catchments (e.g., Han et al., 2020; Klos et al., 2023; White et al., 2019). It is noted that aforementioned studies only have limited information on the subsurface CZ structure of the sites (i.e., the depth extent of structurally distinct layers such as soil and weathered rock), which are spatially heterogeneous in a catchment, even at the hillslope scale (e.g., Riebe et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The subsurface critical zone (CZ) structure has been invoked in their study to explain the observed overproduction of streamflow (Wlostowski et al., 2021). Similarly, other studies also used the subsurface CZ structure to explain various hydrologic observations in a number of catchments (e.g., Han et al., 2020; Klos et al., 2023; White et al., 2019). It is noted that aforementioned studies only have limited information on the subsurface CZ structure of the sites (i.e., the depth extent of structurally distinct layers such as soil and weathered rock), which are spatially heterogeneous in a catchment, even at the hillslope scale (e.g., Riebe et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the snow season will be shortened due to the temperature increase. Klos et al (2023) have shown that snow deficit in winter and drought lead to reduced soil surface saturation in a wetland area under a Mediterranean climate. Therefore, a strong impact on the carbon cycling within mountainous peatlands of the Pyrenees is expected.…”
Section: Introductionmentioning
confidence: 99%